2017
DOI: 10.15761/gmo.1000121
|View full text |Cite
|
Sign up to set email alerts
|

Biological evaluations of novel 2,3,3-Trisphosphonate in osteoclastic and osteoblastic activities

Abstract: Bisphosphonates (BPs) are the first line treatment for many bone diseases including hypercalcimia associated with bone malignancies. In this paper, we introduce a new analogue of bisphosphonate called the 2,3,3-Trisphosphonate (2,3,3-TriPP) that was synthesised in a two steps reaction. In vitro investigations using a medically known bisphosphonate (Etidronate) and the 2,3,3-TrisPP were performed with an aim to evaluate biological effect of this novel compound in major bone cells. 2,3,3-TrisPP showed to have po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Similar to pyrophosphate, bisphosphonates exhibit a high affinity for bone hydroxyapatite and effectively prevent calcification [44]. The Food and Drug Administration (FDA) currently approves some of these compounds for the treatment of bone resorption, Paget's disease, osteoporosis, multiple myeloma, hypercalcemia associated with bone metastasis, and fibrous dysplasia [14,15,45]. On the other hand, in addition to their capacity as inhibitors of bone resorption, bisphosphonates are antimicrobial agents [46], anticancer agents [47], selective inhibitors of acid sphingomyelinase, and stimulators of γδ-T lymphocytes [48].…”
Section: Chemical and Biological Characteristics Of Bisphosphonate-based Compoundsmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar to pyrophosphate, bisphosphonates exhibit a high affinity for bone hydroxyapatite and effectively prevent calcification [44]. The Food and Drug Administration (FDA) currently approves some of these compounds for the treatment of bone resorption, Paget's disease, osteoporosis, multiple myeloma, hypercalcemia associated with bone metastasis, and fibrous dysplasia [14,15,45]. On the other hand, in addition to their capacity as inhibitors of bone resorption, bisphosphonates are antimicrobial agents [46], anticancer agents [47], selective inhibitors of acid sphingomyelinase, and stimulators of γδ-T lymphocytes [48].…”
Section: Chemical and Biological Characteristics Of Bisphosphonate-based Compoundsmentioning
confidence: 99%
“…Disorders in this metabolic pathway can cause toxicity, alteration of cellular structure and function, as well as loss of homeostasis [84]. Experimental evidence has shown that second-and third-generation nitrogenous bisphosphonates are generally more potent than conventional bisphosphonates in inhibiting bone resorption [14,82]. However, the main disadvantage of administering these compounds is related to toxicity, as it can induce the development of severe osteonecrosis and gastric inflammation in humans [70,86].…”
Section: Chemical and Biological Characteristics Of Bisphosphonate-based Compoundsmentioning
confidence: 99%
See 3 more Smart Citations